PENDEKATAN PENGAJARAN INOVATIF UNTUK PENGEMBANGAN PEMIKIRAN KREATIF PADA SISWA SEKOLAH MENENGAH - Jati, Rocky Prasetyo; Pinontoan, Nexen Alexandre; Kristanty, Shinta (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
Creative thinking has a crucial role in the digital era and artificial intelligence (AI) today. Community Service Activities (PKM) aims to develop creative thinking in secondary education through innovative teaching methods such as creative content production. PKM activities written in this article were carried out at Asysyakirin Islamic High School, Tangerang. Activities use a participatory action research approach (PAR), which involves collaboration between researchers and participants. PAR steps include needs analysis, program planning, script development, technical assistance, content production, training, and evaluation. The results showed a significant increase in student involvement and creative thinking skills. The use of creative content creates a dynamic and interactive learning environment, changing students from passive recipients to active creators. Creative content provides learning flexibility that helps reduce absence and supports various learning styles. The process of making creative content encourages students to think critically and creatively while improving their technical skills. As a result, students show improved academic performance and creative thinking skills. Implementation of creative content production in Asysyakirin Islamic High School shows the potential of digital tools to change the educational experience. Recommendations for further development include sustainable content production, advanced training, collaborative network, routine evaluation, broader technological integration, technical support, and recognition and incentives. By adopting this method, educational institutions can create a more interesting and effective learning environment, preparing students for future challenges.